2020
DOI: 10.1016/j.sjbs.2020.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of weight loss predictors in severe-morbid obesity patients in the Saudi population

Abstract: Universally, obesity has been affected more than 650 million and converts as global health problem. Obesity is equally affecting starting from children to elder population. Obese subjects are converting into severe obese and then into morbid obesity. Body mass index is proning from 30 to 50 kg/m 2 in the adult population. Obesity is connected with the future complications of hypertension, type 2 diabetes mellitus, cardiovascular, stroke, osteoarthritis, obstructive sleep apnea and liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Additionally, we observed an association between pain intensity and backpack-carrying style in adolescents, which has also been reported elsewhere [ 24 ]. Furthermore, our study revealed an impact of BMI on adolescents’ quality of life and physical activities, consistent with several previous studies [ 24 , 25 , 26 , 27 ]. However, one study reported contradictory results regarding this relationship [ 10 ].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, we observed an association between pain intensity and backpack-carrying style in adolescents, which has also been reported elsewhere [ 24 ]. Furthermore, our study revealed an impact of BMI on adolescents’ quality of life and physical activities, consistent with several previous studies [ 24 , 25 , 26 , 27 ]. However, one study reported contradictory results regarding this relationship [ 10 ].…”
Section: Discussionsupporting
confidence: 93%
“…Patients must decide on the optimum technique under the doctors' guidance based on their body weight, personal medical history, and family medical history. Nevertheless, patients must go through postoperative monitoring to contact surgeons [5].…”
Section: Consequences Of Obesity In Increasing Risk Factorsmentioning
confidence: 99%
“…These include nausea, vomiting, abdominal pain, intestinal obstruction, diarrhea, and nutritional deficiencies. Until and unless the patient commits to maintaining and observing regular physical activity and a diet control plan, the postoperative effects of bariatric surgery will not support the expectations [ 14 ]. Most cases require a nutritious diet with enough hydration, minerals, multivitamins, and fewer fats and carbohydrates [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Until and unless the patient commits to maintaining and observing regular physical activity and a diet control plan, the postoperative effects of bariatric surgery will not support the expectations [ 14 ]. Most cases require a nutritious diet with enough hydration, minerals, multivitamins, and fewer fats and carbohydrates [ 14 ]. Bariatric surgery can improve the quality of life, but long-term consequences must be avoided through proper follow-up [ 15 ].…”
Section: Introductionmentioning
confidence: 99%